Domestic Migration and the Risk of Households Being Defrauded in Urban China - Ye, Mengqian; Lian, Nan; Lai, Jennifer (Frontiers in Human Dynamics, 2022)
This paper investigates whether domestic migration of households in urban China has any impact on their risks of being defrauded. By utilizing China Household Finance Survey (CHFS) in 2015, we find that domestic migration is significantly positively related to households’ risk of being defrauded. After controlling the corresponding individual and household characteristics, the result indicates that the probability of being defrauded with any losses and the amount of money being defrauded of migrant households in urban areas increased significantly by 0.98% and 7.43% compared to local urban households, respectively. This positive relationship between the risk of being defrauded and migration status of households is mainly concentrated in eastern China and highly educated households. Besides, the baseline results remain robust when we perform robustness checks, including the IV estimation which tackles the potential endogeneity of the migration status of the household head. Furthermore, we find that migrant households with less local social networks or less satisfaction of the current level of social security tend to be defrauded more intensively. The findings call for reflections on policies of domestic migration and urbanization, and still their unintentional consequences of social integration and security.